2009
DOI: 10.1039/b905068j
|View full text |Cite
|
Sign up to set email alerts
|

Generation of potent and selective kinase inhibitors by combinatorial biosynthesis of glycosylated indolocarbazoles

Abstract: We report the generation of novel glycosylated indolocarbazoles by combinatorial biosynthesis, and the identification of two novel potent and selective compounds inhibitors of JAK2 and Ikkb kinases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 15 publications
0
53
0
Order By: Relevance
“…EC-70124 is a product of metabolic engineering of the staurosporine and rebeccanycin biosynthetic pathways. In biochemical kinase assays, EC-70124 acted as a highly effective multikinase inhibitor (37). We show here that both in cells and tumor xenografts, the efficacy of EC-70124 depended on the cell context and activation state of the STAT3 and NF-kB pathways.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…EC-70124 is a product of metabolic engineering of the staurosporine and rebeccanycin biosynthetic pathways. In biochemical kinase assays, EC-70124 acted as a highly effective multikinase inhibitor (37). We show here that both in cells and tumor xenografts, the efficacy of EC-70124 depended on the cell context and activation state of the STAT3 and NF-kB pathways.…”
Section: Discussionmentioning
confidence: 89%
“…Assays interrogating in vitro a large spectrum of kinases in the human kinome revealed that EC-70124 was highly active against IKK and JAK kinases (37,38). EC-70124 was also reported to inhibit NF-kB and JAK/STAT signaling, respectively, in glioblastoma cells (43) and in triple-negative breast cancer cells (38).…”
Section: Ec-70124 Inhibits Nf-kb and Stat3 In Prostate Cancer Cellsmentioning
confidence: 99%
See 2 more Smart Citations
“…Persistent blockade of the NFkB pathway by a smallmolecule inhibitor induces a senescence phenotype in GICs undergoing differentiation In order to translate our findings into a more pharmacologically relevant setting, we used a recently described glycosylated indolocarbazol, 70124 (compound 8), with a potent (o30 pM) IKK2 inhibition activity (Sanchez et al, 2009), in our differentiation model. We showed that treatment of differentiated GICs Consistent with our previous data using the genetic strategies, treatment of differentiating GICs with 70124 resulted in upregulated mRNA expression of neuronal markers Tuj1 and MAP2 and downregulation of GFAP and, to a lesser extent, S100B ( Figure 5c).…”
Section: Downmodulation Of Nfkb Activity Accelerates Maturation Of DImentioning
confidence: 99%